Composite solder and preparation method and packaging method thereof

By using plasma chemical vapor deposition technology to grow nanographene in tin-silver copper solder, and combining metal nickel and metal titanium additives, composite solder is prepared, which solves the shortcomings of traditional solder in terms of solder strength and thermal expansion stress, and achieves efficient welding strength improvement and thermal expansion coefficient gradient transition.

CN115846934BActive Publication Date: 2025-04-29GUANGDONG HUAZHIXIN ELECTRONIC TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211590640.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-04-29
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The existing tin-silver copper solder has shortcomings in improving welding strength and reducing thermal expansion stress concentration. Especially in the welding process between metals and ceramics, traditional nanoparticle reinforcement is prone to coarse or react in high temperature environments, resulting in a decrease in welding quality.

Method used

Nanographene is grown in the base solder by plasma chemical vapor deposition technology, and a composite solder is prepared by combining metal nickel and metal titanium as additives. This method not only enhances the fine-grained structure of the solder, but also realizes a gradient transition between the thermal expansion coefficient between ceramic-solder-metal.

Benefits of technology

It effectively improves the solder strength, reduces stress concentration during the welding process, improves welding quality, and solves the solder flow problem caused by the prone agglomeration of nanographene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115846934B_ABST
    Figure CN115846934B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite solder and a preparation method thereof, a packaging method, and a composite solder preparation method comprising the following steps: providing a basic solder, wherein the basic solder composition comprises 20% to 35% of metallic copper, 55% to 70% of metallic silver, and 10% to 15% of an auxiliary agent, wherein the mass ratio of metallic silver to metallic copper is (20 to 35): (50 to 70); placing metallic silver and metallic copper in an atmosphere containing a carbon source gas for plasma chemical vapor deposition treatment, preparing a prefabricated solder, and mixing the prefabricated solder and the auxiliary agent. Plasma enhanced chemical vapor deposition is used to in-situ grow nanographene on a basic solder containing metallic silver and metallic copper, the grown graphene is dispersedly distributed, and fine crystal strengthening can solve the problem that graphene is easy to agglomerate and hinder the flow of solder to cause hole formation, and the prepared composite solder can effectively improve the welding strength and realize the gradient transition of thermal expansion coefficient between ceramic-solder-metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electronic packaging, and in particular to a composite solder and a preparation method and a packaging method thereof. Background Art

[0002] Microelectronic packaging is an important component of electronic products. Its main function is to provide electronic products with electrical and thermal paths and to protect them from the impact of the external environment. The cost, performance, size and weight of electronic products largely depend on the structure and materials of the packaging.

[0003] At present, silver-copper solder has been widely used as an electronic packaging interconnection material in electronic products through brazing. However, the increase in the packaging density of electronic products and the reduction in the size of solder joints have put forward higher requirements on the strength of solder products. Brazing refers to a welding method in which the solder and the weldment are heated to the melting temperature of the solder at the same time, and the gap between the solid workpieces is filled with liquid solder to connect the metals. For the solder, on the one hand, it is necessary to ensure that the solder has excellent ductility, and on the other hand, it is necessary to ensure that it has high strength, so that sufficient slip can occur, and the misalignment cannot be excessively accumulated to cause serious stress concentration.

[0004] The traditional method to improve the tin-silver-copper solder is to add tiny particles to the tin-silver-copper solder and achieve strengthening by means of the dispersion strengthening effect of the tiny particles. Among them, nanoparticles have a more obvious strengthening effect than micron particles, so they have received widespread attention. The nanoparticles used to strengthen the tin-silver-copper solder mainly include metal nanoparticles such as Ag, Al, Mo, Co and Ni, and non-metallic nanoparticles such as TiO2 and Al2O3. However, due to the large difference in thermal expansion coefficients for welding metals and ceramics, the residual stress of the brazed joint is large, which reduces the brazing quality. In addition, traditional reinforcing phases such as metal nanoparticles are prone to coarsening or excessive reaction with silver-copper alloys during the welding process and high temperature environment, and lose their strengthening effect, while non-metallic nanoparticles are not easy to form a reliable interface with tin-silver-copper alloys, which is not conducive to the strength and thermal fatigue resistance of solder joints. Furthermore, traditional nanoparticles are prone to be lost in large quantities with the flux during the reflow soldering process, affecting the final welding effect. In addition, the production of nanographene (VFG) is difficult to control: for example, the mechanical exfoliation method is inefficient and prone to agglomeration; the redox method is difficult to ensure complete reaction; and the epitaxial growth method is not easy to transfer VFG. Summary of the invention

[0005] Based on this, in order to improve the welding strength between metal and ceramic and achieve a gradient transition of the thermal expansion coefficient, it is necessary to provide a composite solder and a preparation method and a packaging method thereof.

[0006] The present invention provides a method for preparing a composite solder, comprising the following steps:

[0007] A basic solder is provided, wherein the basic solder comprises, by weight percentage, 20% to 35% of metallic copper, 55% to 70% of metallic silver, and 10% to 15% of an auxiliary agent, wherein the particle sizes of the metallic silver and the metallic copper are 50 nm to 200 nm, and the mass ratio of the metallic silver to the metallic copper is (20 to 35):(50 to 70);

[0008] Placing the metallic silver and the metallic copper in an atmosphere containing a carbon source gas for plasma chemical vapor deposition treatment to prepare a prefabricated solder, wherein the radio frequency power of the plasma chemical vapor deposition treatment is 150W to 250W;

[0009] The pre-solder and the additive are mixed.

[0010] In one embodiment, the auxiliary agent includes a metal reinforcing agent, a flux, a surfactant, a thixotropic agent, a thickener and a diffusing agent in a weight ratio of (1-5):(2-4):(1-3):(0.5-2):(1-3):(1-3).

[0011] In one embodiment, the metal reinforcing agent includes metal nickel and metal titanium, and the mass ratio between the metal nickel and the metal titanium is (1-3):(0.5-2).

[0012] In one embodiment, the particle size of the metal nickel and the metal titanium is 50nm to 300nm.

[0013] In one embodiment, the composition of the basic solder comprises, by weight percentage:

[0014]

[0015] In one embodiment, the atmosphere further comprises an inert gas, wherein the molar content of the carbon source gas is 80% to 99%, and the molar content of the inert gas is 1% to 20%.

[0016] In one embodiment, the plasma chemical vapor deposition process satisfies one or more of the following characteristics:

[0017] (1) The processing temperature is 600℃~750℃;

[0018] (2) The processing time is 1h to 3.5h;

[0019] (3) The processing pressure is 400Pa~1000Pa.

[0020] In one embodiment, the metal silver and the metal copper further include:

[0021] The metallic silver and the metallic copper are placed in a protective gas atmosphere, and heated to 600° C. to 750° C. at a pressure of 180 Pa to 220 Pa for a heating time of 15 minutes to 90 minutes.

[0022] The present invention also provides a composite solder prepared according to the preparation method described in any one of claims 1 to 8.

[0023] The present invention further provides a packaging method, in which a ceramic component and a metal component are connected by the above-mentioned composite solder and then subjected to brazing treatment.

[0024] Nanographene is grown in situ on a base solder containing metallic silver and metallic copper using plasma enhanced chemical vapor deposition. The grown graphene is dispersed and finely grained, which can solve the problem of graphene agglomeration hindering solder flow and causing hole formation. The prepared composite solder can effectively improve the soldering strength and achieve a gradient transition of the thermal expansion coefficient between ceramic-solder-metal. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a graph showing the test results of the flatness of the joint formed by the composite solder of Example 1;

[0026] Figure 2 This is a graph showing the test results of the joint flatness formed by the composite solder of Comparative Example 2;

[0027] Figure 3 This is a graph showing the test result of the joint flatness formed by the composite solder of Comparative Example 3;

[0028] Figure 4 This is a graph showing the test results of the joint wetting angle formed by the composite solder of Example 1;

[0029] Figure 5 This is a graph showing the test results of the joint wetting angle formed by the composite solder of Comparative Example 2. DETAILED DESCRIPTION

[0030] The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not itself indicate the relationship between the various embodiments and / or settings discussed.

[0031] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the invention, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present invention, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0032] Unless otherwise indicated, all percentages, fractions and ratios are calculated based on the total mass of the composition of the present invention. Unless otherwise indicated, all masses of listed ingredients are given as active substances, so they do not include solvents or by-products that may be contained in commercially available materials. The term "mass percentage content" herein may be represented by the symbol "%".

[0033] As used herein, "includes," "comprising," "including," "containing," "having," or other variations are intended to encompass non-closed inclusions, and no distinction is made between these terms. The term "comprising" means that other steps and ingredients that do not affect the end result may be added. The term "comprising" also includes the terms "consisting of" and "consisting essentially of." The compositions and methods / processes of the present invention comprise, consist of, and consist essentially of the essential elements and limitations described herein, as well as any additional or optional ingredients, components, steps, or limitations described herein. As used herein, no distinction is made between the terms "efficacy," "performance," "effect," and "efficacy."

[0034] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0035] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0037] The present invention provides a method for preparing a composite solder, comprising the following steps:

[0038] Providing a basic solder, the basic solder comprises, by weight percentage, 20% to 35% of metallic copper, 55% to 70% of metallic silver and 10% to 15% of an auxiliary agent, wherein the particle sizes of the metallic silver and the metallic copper are 50nm to 200nm, and the mass ratio of the metallic silver to the metallic copper is (20 to 35):(50 to 70);

[0039] Placing metallic silver and metallic copper in an atmosphere containing a carbon source gas for plasma chemical vapor deposition treatment to prepare a prefabricated solder, wherein the radio frequency power of the plasma chemical vapor deposition treatment is 150W to 250W;

[0040] Mix the preform solder and additives.

[0041] Further, the particle size of metallic silver is 50 μm to 200 μm. It can be understood that the particle size of metallic silver can be but is not limited to 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.

[0042] Furthermore, the particle size of the metallic copper is 50 μm to 200 μm. It can be understood that the particle size of the metallic copper can be but is not limited to 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm. The particle sizes of the metallic silver and the metallic copper do not affect each other and are selected independently.

[0043] It can be understood that the RF power can be, but is not limited to, 150W, 170W, 190W, 200W, 210W, 230W or 250W.

[0044] In a specific example, the additives include a metal reinforcing agent, a flux, a surfactant, a thixotropic agent, a thickener, and a diffusing agent in a weight ratio of (1-5):(2-4):(1-3):(0.5-2):(1-3):(1-3).

[0045] In a specific example, the metal reinforcing agent includes metal nickel and metal titanium, and the mass ratio between the metal nickel and the metal titanium is (1-3):(0.5-2).

[0046] It can be understood that the particle sizes of the metal nickel and the metal titanium are between 50 nm and 300 nm, and the particle sizes of the metal nickel and the metal titanium do not affect each other and are selected independently.

[0047] Furthermore, the auxiliary agent includes metal nickel, metal titanium, flux, surfactant, thixotropic agent, thickener and diffusant in a weight ratio of (1-3):(0.5-2):(2-4):(1-3):(0.5-2):(1-3):(1-3).

[0048] In one specific example, the composition of the base solder includes, by weight percentage:

[0049]

[0050] Preferably, the mass ratio between metallic copper and metallic silver is (20-30):(60-65).

[0051] Further, the soldering flux may be, but is not limited to, selected from resin soldering flux, and preferably, the soldering flux is rosin soldering flux.

[0052] Furthermore, the surfactant is preferably a non-ionic surfactant, which can be but is not limited to one or more selected from fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and N-vinyl amides. Specifically, the surfactant is N-vinyl amide, specifically polyvinyl pyrrolidone.

[0053] In a specific example, the thixotropic agent may be, but is not limited to, at least one selected from fumed silica, organic bentonite, hydrogenated castor oil, and polyamide wax. Preferably, the thixotropic agent is polyamide wax.

[0054] In a specific example, the thickener may be, but is not limited to, at least one selected from the group consisting of xanthan gum, carboxymethyl cellulose and polyethylene glycol. Preferably, the thickener is polyethylene glycol.

[0055] In a specific example, the diffusing agent may be, but is not limited to, selected from zirconium hydride.

[0056] In a specific example, the atmosphere further includes an inert gas, wherein the amount of the carbon source gas is 80% to 99%, and the amount of the inert gas is 1% to 20%.

[0057] Preferably, the pressure ratio of the carbon source gas to the inert gas is 1:(1-8). Specifically, the pressure ratio of the carbon source gas to the inert gas can be but is not limited to 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7 or 1:8.

[0058] In one specific example, the carbon source gas is methane.

[0059] It can be understood that the total flow rate of the carbon source gas and the inert gas in the atmosphere containing the carbon source gas is 100 sccm to 140 sccm. Further, the flow rate can be but is not limited to 100 sccm, 110 sccm, 120 sccm, 130 sccm or 140 sccm.

[0060] Specifically, the inert gas may be, but is not limited to, at least one of argon and nitrogen. In a specific example, the processing temperature in the plasma chemical vapor deposition process is 600° C. to 750° C.

[0061] In a specific example, the processing time in the plasma chemical vapor deposition process is 1 hour to 3.5 hours.

[0062] Furthermore, the processing time in the plasma chemical vapor deposition process may be, but is not limited to, 1 h, 2 h, 3 h or 3.5 h.

[0063] In a specific example, the pressure in the plasma chemical vapor deposition process is 400Pa to 1000Pa.

[0064] Furthermore, the pressure in the plasma chemical vapor deposition process can be, but is not limited to, 400Pa, 500Pa, 600Pa, 700Pa, 750Pa, 800Pa, 850Pa, 900Pa or 1000Pa.

[0065] In a specific example, the metal silver and the metal copper further include, before the plasma chemical vapor deposition process:

[0066] The metallic silver and metallic copper are placed in a protective gas atmosphere, and heated to 600° C. to 750° C. at a pressure of 180 Pa to 220 Pa for a heating time of 15 minutes to 90 minutes.

[0067] It can be understood that the above-mentioned protective atmosphere includes a mixed gas of argon and hydrogen, wherein the content of argon in the protective atmosphere is greater than 80%, and the total flow rate of the protective gas is 80 sccm to 200 sccm.

[0068] The pressure during the above heating may be, but is not limited to, 180Pa, 190Pa, 200Pa, 210Pa or 220Pa.

[0069] Furthermore, the present invention also provides a composite solder prepared according to the above preparation method.

[0070] The specific preparation method of the composite solder comprises the following steps:

[0071] Prepare the raw materials of the basic solder, mix metal copper and metal silver and place them on a plasma chemical vapor deposition stage, evacuate to below 50Pa, introduce a protective gas mixed with argon and hydrogen, wherein the volume ratio of argon and hydrogen is 4:1, heat treat to 600℃~750℃ at a pressure of 180Pa~220Pa, introduce an atmosphere containing a carbon source gas after the temperature reaches the growth temperature, turn off the protective gas, and in the atmosphere containing the carbon source gas, turn on the radio frequency at a pressure of 400Pa~1000Pa for deposition for 1h~3h, turn off the radio frequency, power supply and carbon source gas, stop introducing the remaining gases when the temperature cools to 450℃, cool naturally, take out the above-mentioned prefabricated solder, and mix it with the additive.

[0072] The above-mentioned composite solder uses plasma enhanced chemical vapor deposition to in-situ grow nanographene on a base solder containing metallic silver and metallic copper. The grown graphene is dispersed and finely grained, which can solve the problem that graphene is easy to agglomerate and hinders the flow of solder, leading to the formation of holes. The prepared composite solder can effectively improve the soldering strength and achieve a gradient transition of the thermal expansion coefficient between ceramic-solder-metal.

[0073] The present invention also provides a composite solder prepared according to the above preparation method.

[0074] The present invention further provides a packaging method, in which a ceramic component and a metal component are connected by the above-mentioned composite solder and then subjected to brazing treatment.

[0075] It can be understood that the ceramic component mentioned above can be, but is not limited to, a silicon nitride ceramic component, and the metal component can be, but is not limited to, a copper alloy component.

[0076] The following specific examples are provided to further illustrate the composite solder and the preparation method of the present invention in detail. Unless otherwise specified, the raw materials involved in the following specific embodiments can all be commercially available.

[0077] Example 1

[0078] The present embodiment provides a composite solder, which comprises, by weight percentage, 25% of metal copper, 63% of metal silver, 2% of metal nickel, 1% of metal titanium, 2% of flux, 2% of surfactant, 1% of thixotropic agent, 2% of thickener and 2% of diffusant.

[0079] The thickener is polyethylene glycol, the diffusing agent is zirconium hydride, the soldering flux is rosin soldering flux, the surfactant is polyvinyl pyrrolidone, and the thixotropic agent is preferably polyamide wax.

[0080] The preparation steps of the above composite solder are as follows:

[0081] Prepare the raw materials of the basic solder, mix metal copper and metal silver and place them on the plasma chemical vapor deposition stage, evacuate to below 10Pa, introduce a protective gas mixed with argon and hydrogen in a volume ratio of 4:1, control the protective gas flow rate to 100sccm, heat to 600℃~750℃ under a pressure of 200Pa, and introduce a mixed gas of methane and argon (the pressure ratio of methane and argon is 1:4) after the temperature reaches the growth temperature. The total flow rate of the mixed gas is 100sccm, control to turn off the protective gas, turn on the radio frequency and deposit for 2 hours at a pressure of 800Pa, then turn off the radio frequency, power supply and methane gas, stop introducing argon when the temperature cools to 450℃, let it cool naturally, take out the above-mentioned prefabricated solder, and mix it with the additive to obtain a composite solder.

[0082] Comparative Example 1

[0083] The comparative example provides a composite solder, which comprises, by weight percentage, 5% of metal copper, 83% of metal silver, 2% of metal nickel, 1% of metal titanium, 2% of flux, 2% of surfactant, 1% of thixotropic agent, 2% of thickener and 2% of diffusing agent.

[0084] The thickener is polyethylene glycol, the diffusing agent is zirconium hydride, the soldering flux is rosin soldering flux, the surfactant is polyvinyl pyrrolidone, and the thixotropic agent is preferably polyamide wax.

[0085] The preparation steps of the above composite solder are as follows:

[0086] Prepare the raw materials of the basic solder, mix metal copper and metal silver and place them on the plasma chemical vapor deposition stage, evacuate to below 10Pa, introduce a protective gas mixed with argon and hydrogen in a volume ratio of 4:1, control the protective gas flow rate to 100sccm, heat to 600℃~750℃ under a pressure of 200Pa, and introduce a mixed gas of methane and argon (the pressure ratio of methane and argon is 1:4) after the temperature reaches the growth temperature. The total flow rate of the mixed gas is 100sccm, control to turn off the protective gas, turn on the radio frequency and deposit for 2 hours at a pressure of 800Pa, then turn off the radio frequency, power supply and methane gas, stop introducing argon when the temperature cools to 450℃, let it cool naturally, take out the above-mentioned prefabricated solder, and mix it with the additive to obtain a composite solder.

[0087] Comparative Example 2

[0088] The comparative example provides a composite solder, which comprises, by weight percentage, 15% of metal copper, 73% of metal silver, 2% of metal nickel, 1% of metal titanium, 2% of flux, 2% of surfactant, 1% of thixotropic agent, 2% of thickener and 2% of diffusing agent.

[0089] The thickener is polyethylene glycol, the diffusing agent is zirconium hydride, the soldering flux is rosin soldering flux, the surfactant is polyvinyl pyrrolidone, and the thixotropic agent is preferably polyamide wax.

[0090] The preparation steps of the above composite solder are as follows:

[0091] Prepare the raw materials of the basic solder, mix metal copper and metal silver and place them on the plasma chemical vapor deposition stage, evacuate to below 10Pa, introduce a protective gas mixed with argon and hydrogen in a volume ratio of 4:1, control the protective gas flow rate to 100sccm, heat to 600℃~750℃ under a pressure of 200Pa, and introduce a mixed gas of methane and argon (the pressure ratio of methane and argon is 1:4) after the temperature reaches the growth temperature. The total flow rate of the mixed gas is 100sccm, control to turn off the protective gas, turn on the radio frequency and deposit for 2 hours at a pressure of 800Pa, then turn off the radio frequency, power supply and methane gas, stop introducing argon when the temperature cools to 450℃, let it cool naturally, take out the above-mentioned prefabricated solder, and mix it with the additive to obtain a composite solder.

[0092] Comparative Example 3

[0093] The comparative example provides a composite solder, which comprises, by weight percentage, 40% of metal copper, 48% of metal silver, 2% of metal nickel, 1% of metal titanium, 2% of flux, 2% of surfactant, 1% of thixotropic agent, 2% of thickener and 2% of diffusing agent.

[0094] The thickener is polyethylene glycol, the diffusing agent is zirconium hydride, the soldering flux is rosin soldering flux, the surfactant is polyvinyl pyrrolidone, and the thixotropic agent is preferably polyamide wax.

[0095] The preparation steps of the above composite solder are as follows:

[0096] Prepare the raw materials of the basic solder, mix metal copper and metal silver and place them on the plasma chemical vapor deposition stage, evacuate to below 10Pa, introduce a protective gas mixed with argon and hydrogen in a volume ratio of 4:1, control the protective gas flow rate to 100sccm, heat to 600℃~750℃ under a pressure of 200Pa, and introduce a mixed gas of methane and argon (the pressure ratio of methane and argon is 1:4) after the temperature reaches the growth temperature. The total flow rate of the mixed gas is 100sccm, control to turn off the protective gas, turn on the radio frequency and deposit for 2 hours at a pressure of 800Pa, then turn off the radio frequency, power supply and methane gas, stop introducing argon when the temperature cools to 450℃, let it cool naturally, take out the above-mentioned prefabricated solder, and mix it with the additive to obtain a composite solder.

[0097] The copper alloy and silicon nitride Si3N4 ceramic are connected by the composite solder of the above embodiment and the comparative example. The copper alloy and silicon nitride ceramic are both in horizontal position before welding. The two are welded by solder. The flatness of the copper surface (silicon nitride at the bottom) after welding can be compared to reflect the effect of solder on flatness. The test results are shown in the following table. Figure 1 to Figure 3 These are the joint flatness test diagrams formed by the composite solders of Example 1, Comparative Example 2 and Comparative Example 3 respectively;

[0098] Flatness Copper powder ratio First Test Second test Third test Fourth test average Face shape Comparative Example 1 5% 21.49 21.81 55.93 22.16 30.35 Smiley Face Comparative Example 2 15% 24.41 21.83 5.11 23.11 18.62 Smiley Face Comparative Example 3 40% 31.88 5.78 36 31.69 26.34 Crying Face Example 1 25% 2.13 6.88 2.67 10.58 5.57 Smiley Face

[0099] It can be seen from the above table that when the amount of copper powder added to the basic solder is 25% and the amount of silver powder added is 63%, the flatness is greatly improved, which can effectively regulate the thermal expansion coefficient of the brazing joint and the interface reaction. The lower the flatness, the better the thermal expansion match between the solder and the ceramic and metal, which means the greatest improvement in the thermal expansion coefficient of the brazing joint and the interface reaction.

[0100] Furthermore, the wetting angle of the above joints was further tested, and the test results are shown in the following table: Figure 4-5 They are test diagrams of joint wetting angle formed by composite solders of Example 1 and Comparative Example 2;

[0101]

[0102] It can also be seen from the above wetting angle test results that when the proportion of nano copper powder in the basic solder is below 25%, as the proportion of nano copper powder increases, the ratio between metal copper powder and metal silver powder changes, resulting in the wetting angle of the solder joint forming a continuous decrease, and the corresponding wettability continues to increase. When the copper powder ratio is 40% and the silver powder ratio is 48%, the solder wetting angle decreases instead of increasing, and the wettability decreases, indicating that the optimal addition amount of copper powder in the basic solder is 25%, and the addition amount of silver powder is 63%, that is, the ratio between copper powder and silver powder is 25:63, which is the most suitable.

[0103] The above-mentioned composite solder uses plasma enhanced chemical vapor deposition to in-situ grow nanographene on a base solder containing metallic silver and metallic copper. The grown graphene is dispersed and finely grained, which can solve the problem that graphene is easy to agglomerate and hinders the flow of solder, leading to the formation of holes. The prepared composite solder can effectively improve the soldering strength and achieve a gradient transition of the thermal expansion coefficient between ceramic-solder-metal.

[0104] The technical features of the above embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0105] The above-described embodiments only express several implementation methods of the present invention, which are convenient for understanding the technical solutions of the present invention in detail, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.

Claims

1. A method for preparing a composite solder, characterized in that: The following steps are involved: A basic solder is provided, wherein the basic solder comprises, by weight percentage, 20% to 35% of metallic copper, 55% to 70% of metallic silver and 10% to 15% of an auxiliary agent, wherein the particle size of the metallic silver and the metallic copper is 50nm to 200nm; the auxiliary agent comprises a metal reinforcing agent, a soldering flux, a surfactant, a thixotropic agent, a thickener and a diffusing agent in a weight ratio of (1 to 5):(2 to 4):(1 to 3):(0.5 to 2):(1 to 3):(1 to 3); the metal reinforcing agent comprises metallic nickel and metallic titanium, and the mass ratio between the metallic nickel and the metallic titanium is (1 to 3):(0.5 to 2); Placing the metallic silver and the metallic copper in an atmosphere containing a carbon source gas for plasma chemical vapor deposition treatment to prepare a prefabricated solder, wherein the radio frequency power of the plasma chemical vapor deposition treatment is 150W to 250W; The pre-solder and the additive are mixed.

2. The method for preparing the composite solder according to claim 1, characterized in that: The mass ratio between metallic copper and metallic silver is (20-30):(60-65).

3. The method for preparing the composite solder according to claim 1, characterized in that: The particle sizes of the metal nickel and the metal titanium are each independently 50 nm to 300 nm.

4. The method for preparing the composite solder according to claim 1, characterized in that: In terms of weight percentage, the composition of the basic solder includes: Metallic copper 20% to 30%, 60% to 70% metallic silver, and Additives 10%~15%.

5. The method for preparing the composite solder according to claim 1, characterized in that: The atmosphere further comprises an inert gas, wherein the amount of the carbon source gas is 80% to 99% and the amount of the inert gas is 1% to 20%.

6. The method for preparing the composite solder according to claim 1, characterized in that: The plasma chemical vapor deposition process satisfies one or more of the following characteristics: (1) The processing temperature is 600℃~750℃; (2) The processing time is 1h to 3.5h; (3) The processing pressure is 400Pa~1000Pa.

7. The method for preparing the composite solder according to any one of claims 1 to 6, characterized in that: The metal silver and the metal copper further include, before being subjected to plasma chemical vapor deposition treatment: The metallic silver and the metallic copper are placed in a protective gas atmosphere, and heated to 600° C. to 750° C. at a pressure of 180 Pa to 220 Pa for a heating time of 15 minutes to 90 minutes.

8. A composite solder, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

9. A packaging method, characterized in that: The ceramic part and the metal part are connected by the composite solder as claimed in claim 8 and brazed.

10. The packaging method according to claim 9, characterized in that: The ceramic component comprises a silicon nitride ceramic component; and / or The metal member includes a copper alloy member.

Citation Information

Patent Citations

  • Method for efficiently preparing graphene-reinforcing copper-based composite brazing filler metal at low temperature

    CN103817466A

  • Preparation method of solder pulp for ceramic packaging, ceramic and packaging method of ceramic

    CN109604859A

  • Composite solder for cermet and alloy brazing and preparation method thereof

    CN111037150A